2021
DOI: 10.1101/2021.01.29.428834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SARS-CoV-2 Y453F mink variant displays a striking increase in ACE-2 affinity but does not challenge antibody neutralization

Abstract: SARS-CoV-2 transmission from humans to animals has been reported for many domesticated species, including cats, dogs and minks. Identification of novel spike gene mutations appearing in minks has raised major concerns about potential immune evasion and challenges for the global vaccine strategy. The genetic variant, known as “cluster-five”, arose among farmed minks in Denmark and resulted in a complete shutdown of the world’s largest mink production. However, the functional properties of this new variant are n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…7). Thus, the complex structure reported here provides the molecular explanation why Mink-Y453F RBD demonstrated an increased binding affinity for hACE2 when compared to WT RBD, which is observed in this and previous studies 20,21 .…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…7). Thus, the complex structure reported here provides the molecular explanation why Mink-Y453F RBD demonstrated an increased binding affinity for hACE2 when compared to WT RBD, which is observed in this and previous studies 20,21 .…”
Section: Resultssupporting
confidence: 82%
“…Although we and other groups found a higher binding affinity of Mink-Y453F RBD to hACE2 compared with WT RBD 20,21 , it has been reported that the OH group of RBD Y453 is involved in direct interaction with hACE2 H34 in the cryo-electron microscopy (cryo-EM) complex structure of full-length hACE2 bound to RBD and B 0 AT1 (with the resolution of 2.9 Å) 24 . Interestingly, this interaction was not observed in the crystal complex structures of the hACE2 ectodomain bound to RBD (PDB: 6LZG and 6M0J) (with the resolution of 2.5 Å) or bound to Mink-Y453F RBD in this study (with the resolution of 2.4 Å).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Cluster 5 (also known as “ΔFVI-spike”): Some researchers found that mutation Y453F in the RBD of S protein of this variant did not reduce existing humoral immunity or affect the neutralization response, but it increased transmissibility due to its enhanced affinity with ACE2 ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…It does not decrease established humoural immunity or affect the neutralising response in a vaccine model based on wild‐type RBD or Spike. However, it binds the human ACE‐2 receptor with a fourfold higher affinity suggesting an enhanced transmission capacity 130 . Following the lockdown and mass‐testing, Danish State Serum Institute (SSI) announced on 19 November 2020 that Cluster 5 in all probability had become extinct.…”
Section: Variants Of Concernmentioning
confidence: 99%